2014
DOI: 10.1123/japa.2013-0001
|View full text |Cite
|
Sign up to set email alerts
|

The Braking Force in Walking: Age-Related Differences and Improvement in Older Adults With Exergame Training

Abstract: The purposes of this present research were, in the first study, to determine whether age impacts a measure of postural control (the braking force in walking) and, in a second study, to determine whether exergame training in physically-simulated sport activity would show transfer, increasing the braking force in walking and also improving balance assessed by clinical measures, functional fitness, and health-related quality of life in older adults. For the second study, the authors developed an active video game… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(71 citation statements)
references
References 0 publications
4
67
0
Order By: Relevance
“…This result is similar to that verified by Maillot et al (2014) with the same test after a 12 weeks' intervention by means of sporting exergame. Games such as boxing, tennis, table tennis and bowling, included in the intervention program, require a major involvement of the upper limbs, contributing to the increase of the arm curl test's outcome.…”
Section: Jpes ®supporting
confidence: 79%
See 4 more Smart Citations
“…This result is similar to that verified by Maillot et al (2014) with the same test after a 12 weeks' intervention by means of sporting exergame. Games such as boxing, tennis, table tennis and bowling, included in the intervention program, require a major involvement of the upper limbs, contributing to the increase of the arm curl test's outcome.…”
Section: Jpes ®supporting
confidence: 79%
“…Although the aerobic group showed an improvement in the 2MST performance, the differences were not significant. Positive effects on aerobic endurance after interventions with sports exergame have been previously documented (Maillot et al, 2012;Maillot et al, 2014). Maillot et al (2012) found increased endurance (14%) after intervention with sports exergame assessed by the 6-minute walk test.…”
Section: Jpes ®mentioning
confidence: 90%
See 3 more Smart Citations